STRENGTHENING LHKPN: PREVENTION OF ILLICIT ENRICHMENT IN EFFORTS TO ERADICATE CORRUPTION - Vita Mahardhika (Audito Comparative Law Journal (ACLJ), 2021)
This research aimed to discuss State Organizer's Asset Report or Laporan Harta Kekayaan Pejabat Negara (LHKPN) problems due to the eradication corruption process in Indonesia. This research is normative legal research with a conceptual, historical, and statutory approach. From the research it can be seen that as an effort to prevent illicit enrichment carried out by state officials, it is necessary to strengthen the wealth reports of state administrators, namely by making changes to Law Number 28 of 1999, from collusion, corruption, and nepotism. related to the form and mechanism of the application of sanctions. The recommendation is the law on the Free Implementation of Corruption should be strictly regulated regarding severe administrative sanctions in the form of types of penalties, that directly impact the position of state administrators, and criminal sanctions for state officials who are indicated to have falsified their reporting.